Enseigner la sortie de cadre pour changer les habitudes - Marion M. Bisiaux; Laetitia Fontaine; Nicole Rege Colet (Revue Internationale de Pédagogie de l’Enseignement Supérieur, 2020)
This paper describes a pedagogical innovation carried out by amàco in an engineering school. The purpose of the project was to change conceptions and practices in the field of sustainable building and construction by permeating the instructional design with the core principles of an innovative philosophy based on direct contact with physical matter. After three years of experimenting with matter in the context of seed funding for innovation, a exploratory inquiry based on grounded theory was set up in order to observe the effects on the students’ learning experience and professional development, and the changes in teaching practices for the teachers involved in the project. The results show that the clearest transformations concern the teaching practices that expand well beyond the project. The effects on professional development of students are more slippery to catch although there is good indications that they enter the work force with a vision that takes into account the issues of sustainable building and construction and pays attention to the need to reconnect mankind to his environment.